Architectural Exploration of Blind CFO Estimation in OFDM Systems for Prototyping on a Reconfigurable Platform - Younis, Sedik; Al-Dweik, A.; Sharif, Bayan; Tsimenidis, C. C. (Kurdistan Journal of Applied Research, 2017)
This paper presents two architectures for prototyping an advanced carrier frequency offset (CFO) estimation technique for OFDM systems on field programmable gate array (FPGA). The parallel stream architecture (PSA) exploits the FPGA parallelism while the multiplexed stream architecture (MSA) employs multiplexing for more efficient hardware implementation. The dual-mode of operation for the proposed architectures has been proposed to achieve optimum performance depending on channel conditions. The proposed architectures with different implementation alternatives have been simulated and verified for FPGA implementation using the Xilinx’s DSP design flow. The estimation accuracy and the resource utilization for the proposed architectures have been evaluated. The prototyping results showed that MSA allows for more resource efficient implementation, where a single FFT core can be shared between parallel streams compared with PSA.